A cloud based WSN remote laboratory for user training - Godoy, Pablo (2016)
This paper presents a WSN remote laboratory prototype aimed at user training. The prototype has been deployed on a Cloud Computing infrastructure, in order to take advantage of the benefits that this technology can provide to remote laboratories. An analysis of the state of the art allows to specified the features required for a remote laboratory intended to be applyed in user training. In this paper, the main results of this analysis are presented. Then, the implementation of the main modules that compose the remote laboratory, and the analysis that led to chose a deployment based on Cloud Computing are presented. Some proof of concept experiments to test the applicability to user training were performed and the results are presented in this paper.